2012
DOI: 10.21608/jpp.2012.84195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chicken Manure Levels, Biofertilizers and Some Foliar Application Treatments on Garlic 1. Plant Growth and Leaf Pigments

Abstract: Two field experiments were carried out during the two successive winter seasons of 2008/2009 and 2009/2010 at El-Gemmeiza Agricultural Research Station, Gharbeya Governorate, to evaluate the effect of chicken manure levels, biofertilizers, some foliar application treatments and their interactions on plant growth and leaf pigments of garlic (Allium sativum L.) Sids 40 clone. The obtained results showed that the highest values of plant height, number of leaves/ plant, leaf area , fresh and dry weights/plant, nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The obtained results are in accordance with those reported by Tartoura and El-Saei (2006), Abd El-Mageed et al (2009), El-Morsy et al (2011 and Dawa et al (2012) on garlic.…”
Section: Bulb Traitssupporting
confidence: 93%
See 1 more Smart Citation
“…The obtained results are in accordance with those reported by Tartoura and El-Saei (2006), Abd El-Mageed et al (2009), El-Morsy et al (2011 and Dawa et al (2012) on garlic.…”
Section: Bulb Traitssupporting
confidence: 93%
“…It was reported that the yeast extract had a stimulatory effects on several process in plant such as cell division, chlorophyll formation, synthesis of protein and nucleic acid beside its content of protective agents, i.e., sugars, amino acids, protein and several vitamins (Wanas, 2006). Treated garlic plants with yeast extract as foliar spray had significant effect on vegetative growth, yield and its components as well as bulb quality (El-Morsy et al, 2011;Dawa et al, 2012;Mansour, 2012;Abou El-Khair and Khalil, 2014;Shalaby andEl-Ramady, 2014 andAhmed, 2015) on garlic plants and (Fawzy et al, 2012 andShafeek et al, 2015) on onion plants. Other effects of yeast on plant growth and yield of some vegetable crops El-Greadly, 2007 andFawzy et al, 2010) on beans, (El-Tohamy et al, 2008) on eggplant, (Fathy et al, 2000) on tomato, (El-Desuki and El-Greadly, 2006) on pea, (Ghoname et al, 2010) on sweet pepper, (Ahmed et al, 2011 andAhmed et al, 2013) on potato and Shehata et al (2012) on cucumber.…”
Section: Introductionmentioning
confidence: 99%